Pengaruh Kurs, Produksi, Dan Suku Bunga Terhadap Ekspor Kerajinan Kulit Provinsi Bali - Surya, Ketut Dima; Widanta, A.A. Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 4, April 2015 (pp. 220 - 348), 2015)
Commodities of craft is a leading commodity exports of the province of Bali, because these commodities provide a substantial contribution to the total exports of the province of Bali. One of craft which is able to penetrate the export market it is leather craft. The purpose of this study was to determine the influence of the US dollar exchange rate, leather production, and the interest rates on working capital loans simultaneously and partially on the export of leather craft in Bali period 1991-2012 and leather craft export prospects for the next five years. The test used in this study is multiple linear regression analysis and trend analysis. The results showed that simultaneous significant effect on the export of leather craft Bali Province. Partially, leather production have significant effect, whereas the US dollar exchange rate and interest rates on working capital loans no significant effect on the export of leather craft Bali Province. Export prospects leather craft Bali Province in the next five years is likely to increase.
Keywords: leather; exports; exchange rate; production; interest rate.